Information systems outsourcing : enduring themes, new perspectives and global challenges. - Hirschheim, Rudy A., 1951-; Dibbern, Jens, ....-; Heinzl, Armin, ....- (Berlin : Springer, 2006)
Part I: Overview.- Part II: Determinants of the IS Outsourcing Decision.- Part III: Outsourcing Relationship Issues.- Part IV: Experiences and Outcome of IS Outsourcing.- Part V: Vendor View and Individual Level Perspective.- Part VI: Application Service Providing and Business Process Outsourcing.- VII: Offshoring and Global-Outsourcing.
Keywords: Bedrijfsstrategie; Informatiesystemen; Informatietechnologie